2013
DOI: 10.1136/archdischild-2013-303729
|View full text |Cite
|
Sign up to set email alerts
|

Weekly sport practice and adolescent well-being

Abstract: We found an inverted, U-shaped relationship between weekly sport practice duration and well-being among adolescents. The peak scores of well-being were around 14 h per week of sport practice, corresponding to twice the recommended 7 h. Practicing higher sport durations was an independent risk factor of poor well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…Recent studies have explored the benefits of physical activity in healthy ageing and the reduction of risk factors of chronic diseases [15], its benefits in school-aged children and youth [28], the association between the lack of physical activity in teenagers and mental illnesses [8], the correlation between the lack of exercise and the risk of developing alcohol use disorders [18], the benefits of sport practice in adolescent wellbeing [31] and even the relation between physical activity with the prevention of certain types of cancer [44,54,27], while in the last cases not conclusive results have been found. Other disorders associated to the lack of physical activity have also been thoroughly reviewed [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored the benefits of physical activity in healthy ageing and the reduction of risk factors of chronic diseases [15], its benefits in school-aged children and youth [28], the association between the lack of physical activity in teenagers and mental illnesses [8], the correlation between the lack of exercise and the risk of developing alcohol use disorders [18], the benefits of sport practice in adolescent wellbeing [31] and even the relation between physical activity with the prevention of certain types of cancer [44,54,27], while in the last cases not conclusive results have been found. Other disorders associated to the lack of physical activity have also been thoroughly reviewed [30].…”
Section: Introductionmentioning
confidence: 99%
“…3 The practice of a sport, because of its broad range of positive effects on health and psychological well-being, is often prescribed for overall physical fitness, and is also widely used as part of physicians' clinical practice in healing patients. 4,5 Researchers generally believe that physical activity has a positive effect on mood and anxiety. Intervention studies have described the anxiolytic and anti-depressive effects of exercise in healthy subjects and patients.…”
Section: Introductionmentioning
confidence: 99%
“…The top scores of well-being were around 14 hours for every week of game practice, which compares to double the recommender participation of 7 hours. Nevertheless, the well-being was opposite when rehearsing for more than 17.5 hours for each week (Merglen et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Subsequently, the stays that were utilized may prompt less mistake fluctuation in youngsters' self-reports of their recurrence of consideration in any physical action, diverged from reporting the exact hours consistently (Adachi & Willoughby, 2013). It is though noteworthy to mention that according to Merglen's et al (2014) study, relationship was found between weekly sport practice and adolescent well-being. Youths in the low and high participation groups indicated more than a twofold risk of reporting poor well-being compared to those practicing 7 hours for every week which is suggested.…”
Section: Introductionmentioning
confidence: 99%